Ancient Jewish sciences and the history of knowledge in Second Temple literature - Ben-Dov, Jonathan,Sanders, Seth L. (New York University Press, 2016)
This work explores the tension between the hegemony of central scientific traditions and local scientific enterprises, showing the relevance of ancient data to contemporary postcolonial historiography of science.
10.18574/nyu/9781479823048.001.0001
Keywords: Aufsatzsammlung; Juden; Wissenschaft; Apokalyptik; Science; Ancient; Astronomy; Ancient; Astrology; Hebrew; Judaism and science; Physiognomy